Power system transformation towards renewables: An evaluation of regulatory approaches for network expansion - Jonas Egerer; Juan Rosellón; Wolf-Peter Schill (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We analyze various regulatory regimes for electricity transmission investment in the context of a transformation of the power system towards renewable energy. We study distinctive developments of the generation mix with different implications on network congestion, assuming that a shift from conventional power plants towards renewables may go along with exogenous shocks on transmission requirements, which may be either of temporary or permanent nature. We specifically analyze the relative performance of a combined merchant-regulatory price-cap mechanism, a cost-based rule, and a non-regulated approach in dynamic generation settings. Through application in a stylized two-node network, we find that incentive regulation may perform satisfactorily only when appropriate weights are used. While quasi-ideal weights generally restore the beneficial properties that incentive regulatory mechanisms are well-known for in static settings, pure Laspeyres weights may either lead to overinvestment (stranded investments) or delayed investments as compared to the welfare optimum benchmark. Stranded investments could then be avoided through proper handling of weights. Model results indicate that using average Laspeyres-Paasche weights appears to be an appropriate strategy in the context of permanently or temporarily increasing network congestion. Our analysis motivates further research aimed to characterize optimal regulation for transmission expansion in the context of renewable integration.
Keywords: Q40; Q42; L51; 330; electricity transmission; incentive regulation; renewable integration; Laspeyres/Paasche weights; ideal weights